The Psychological Impact of the Use of AI in Digital Forensics on Criminal Investigators - Dr. Maha Abdulghani Mohammed Ateyah (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
As a transformative technology, Artificial Intelligence (AI) amplified the precision and efficiency of digital forensics investigations following its integration in the criminal investigations domain. This study aimed at exploring the psychological impact of AI and digital forensics on criminal investigations in modern forensic psychology. An online survey was conducted using Google Forms, in which forensic investigators were required to fill in a closed-ended survey. A total of 102 digital forensic investigators agreed to participate in this study and responded to the survey prompts. The GAD-7 scale had a mean score of 9.20, confirming significant instances of “moderate” and “severe” anxiety among participants. The PSS mean score of 21.92 indicates at least “moderate stress” among the forensic investigators included in this study. The collected data confirms a positive linear relationship between AI usage and investigators’ psychological impact (r = .470, p < .001). The adoption of AI in forensic procedures leads to the emergence of numerous psychological issues, such as anxiety and depression, among forensic specialists.